Baker, Herbert (Sir) 1910. Sketches and design based on studies. Design based upon Tomb of Aruns. Design suggested by Tomb of Theron: an Olympian Victor at Agrigentum Sicily. Design suggested by Phillepeion erected at Olympia by Philip of Macedon. Designed after the Nereid Monument at Xanthos in Lycia Asia Minor. Measured drawing of existing Etruscan Tomb of Aruns Albano near Rome. - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir). 1910. Sketches and designs based on studies. Tomb of Aruns. Tomb of Theron, Olympian Victor at Agrigentum Sicily, design suggested by Phillepeion at Olympia by Philip of Macedon, designed after the Nereid Monument at Xanthos in Lycia, Asia Minor, drawing of Etruscan Tomb of Aruns Albano near Rome.
Design based on Tomb of Aruns: watercolour paint and pencil on paper; 304x365. Design suggested by Tomb of Theron, Olympian Victor at Agrigentum Sicily: watercolour paint and pencil on paper: 380x424; design suggested by Phillepeion at Olympia by Philip of Macedon: watercolour, paint and pencil on paper 410x417; designed after the Nereid Monument at Xanthos in Lycia, Asia Minor: watercolour paint and pencil on paper 500x565, drawing of Etruscan Tomb of Aruns Albano near Rome: watercolour paint and pencil on paper 750x495.
Keywords: Baker, Herbert (Sir). 1910. Sketches and designs based on studies. Tomb of Aruns. Tomb of Theron, Olympian Victor at Agrigentum Sicily, design suggested by Phillepeion at Olympia by Philip of Macedon, designed after the Nereid Monument at Xanthos in Lycia, Asia Minor, drawing of Etruscan Tomb of Aruns Albano near Rome.